Uniting Resilience Research and Practice With an Inequalities Approach. (December 2016) - Hart, Angie; Gagnon, Emily; Eryigit-Madzwamuse, Suna; Cameron, Josh; Aranda, Kay; Rathbone, Anne; Heaver, Becky
The concept of resilience has evolved, from an individual-level characteristic to a wider ecological notion that takes into account broader person–environment interactions, generating an increased interest in health and well-being research, practice and policy. At the same time, the research and policy-based attempts to build resilience are increasingly under attack for responsibilizing individuals and maintaining, rather than challenging, the inequitable structure of society. When adversities faced by children and young people result from embedded inequality and social disadvantage, resilience-based knowledge has the potential to influence the wider adversity context. Therefore, it is vital that conceptualizations of resilience encompass this potential for marginalized people to challenge and transform aspects of their adversity, without holding them responsible for the barriers they face. This article outlines and provides examples from an approach that we are taking in our research and practice, which we have called Boingboing resilience. We argue that it is possible to bring resilience research and practice together with a social justice approach, giving equal and simultaneous attention to individuals and to the wider system. To achieve this goal, we suggest future research should have a co-produced and inclusive research design that overcomes the dilemma of agency and responsibility, contains a socially transformative element, and has the potential to empower children, young people, and families.